2021
DOI: 10.2478/jvetres-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic toxicity study of recombinant bovine interferon alpha in rodents

Abstract: Introduction Recombinant bovine interferon alpha (rBoIFN-α) has been demonstrated to have antiviral activity. However, no conduct of acute or chronic toxicity tests has been reported. Material and Methods Specific pathogen-free Sprague Dawley rats were administered doses at different concentrations through intraperitoneal or intravenous injection. After the administration (single for an acute toxicity test over 14 days or dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies have revealed that the chronic poisoning of broilers can be assessed by serum biochemical changes in the suboptimal health status [ 40 ]. The level of serum protein is considered an important indicator of aflatoxicosis in broilers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that the chronic poisoning of broilers can be assessed by serum biochemical changes in the suboptimal health status [ 40 ]. The level of serum protein is considered an important indicator of aflatoxicosis in broilers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%